THE KENOSIS OF THE HOLY SPIRIT AND THE CREATION IN SERGEI BULGAKOV - Xavier, Donizete José; da Silva, Maria Freire (Perspectiva Teológica, 2020)
This article aims to analyze the kenosis of the Holy Spirit as a ChrisÂtian faith’s key to understanding the creation of the world according to Sergei Bulgakov’s thought. The article highlights the soteriological relevance of the Holy Spirit who, in joint action with the Son, divinizes man and the world. The kenosis of the Spirit extends from the creation of the world as it hovered over the waters, through the Transfiguration up to the eschatological consummation of creations as a new heaven and a new earth. In this kenosis the Spirit dwells on the creature and acts on the human condition that is marked by history and fragility. The article emphasizes that it is possible to speak of the kenosis of the Holy Spirit only through an analogy with the kenosis of the Son. In the latter, divine nature has united itself with human nature and has taken it under the shadow of its strength and power. Finally, the article concludes that under the influence of the Holy Spirit who creates and recreates, human beings are challenged to revive an intuition of the original Paradise, one that orients creatures towards an ecological ethic of responsibility aimed at safeguarding creation.